Terrorism and International Tourism Nexus: Evidence from Pakistan - Rauf, Abdur; Siddique, Hafiz Muhammad Abubakar; Saleem, Qasim; Sidra, Sidra (International Journal of Economics and Financial Issues, 2020)
The association among terrorism and tourism is crucial from the macroeconomic perspective as tourism is considered as a vital sector regarding developmental impacts. This analysis conducted to extract the influence of terrorism on tourism in Pakistan, expending the latest dataset and incorporating some additional factors like FDI, human capital, and economic growth for 1980-2016, using ARDL bounds test. The evidence shows that terrorism has an inverse relationship with tourism in the long run that is statistically significant. Economic growth, FDI, and human capital are the increasing factors of tourism. Terrorism may cause to create insecurity and devastating recreational places. There is a need to resolve the issue of terrorism to enhance tourism in Pakistan. It may help tourist authorities to understand the nature of the impact of terrorism on the tourism industry in Pakistan. Keywords: Terrorism, Tourism, ARDL, Human Capital, Economic Growth JEL Classifications: L83, Z32, J24, F43 DOI: https://doi.org/10.32479/ijefi.10674